BLOCKCHAIN TECHNOLOGIES FOR SECURITY AGAINST CYBER ATTACKS - Antonyan Elena Aleksandrovna; Rybakova Olga Sergeevna (Scientific Journal of Pedagogy and Economics, 2020)
The article deals with new technologies for countering cyber attacks that can be aimed at destabilizing public order, large-scale disruption of communication systems, intimidation by imposing one’s will, including on power structures, and, in general, pose an increased threat to the national and information security of the state. Particular attention is paid to blockchain technology, which allows to hide funds aimed at financing criminal, including terrorist activities, including in the information space. Also in the article, the authors present generalized research results as part of the implementation of the RFBR scientific project No. 18-29-16175 "Blockchain technology to counter the risks of cyberterrorism and cyber extremism: a criminal-legal study". Modern cybercrime dictates new challenges to the state, which can no longer be responded to within the space of a single state. Today, the issue of legislative regulation of the interaction of states to prevent cybercrime with the use of new technologies is an acute issue. The most important aspect of the new forms of countering cybercrime is the decentralization of users of anonymous proxy server systems. And if earlier security agencies still had available "loopholes" for direct access to the user’s IP address, now everything has become much more complicated and a comprehensive analysis of the traffic of a particular user is necessary. Scientists also point out that network attacks can contain malicious embedded code, the use of backdoors and much more. Such attacks can be triggered from anywhere in the world because of a computer with a masked IP-address. A new type of warfare, even cyber warfare, is changing the landscape of war itself. This type of war eliminates the need to have physically capable armed forces and requires the need for forces with strong technical capabilities, such as computer skills. Many countries, including Russia, have come to understand that this is a problem and are actively pursuing policies to address it in order to mitigate threats.